ANALISIS RASIO PROFITABILITAS PT. BANK RAKYAT INDONESIA PERIODE 2018 - 2022 - Bobi Prima Dandi Sitorus, (2023)
This Final Project aims to determine the profitability of Bank BRI. The data was obtained from the financial statements of Bank BRI for the period 2018-2022. Over the course of five years, the profitability ratio of Bank BRI experienced a decline in 2020, indicating that the company, as a whole, is relatively healthy because it has not been able to effectively disburse loans. From the analysis of financial performance, Bank BRI has shown the ability to increase revenue or profits for the company by reducing the amount of expenses incurred. In order to improve financial performance, Bank BRI needs to evaluate its management performance by increasing loans and effectively managing assets.